Assessment of heavy metals pollutants in tree bark of tectona grandis sp. from Perlis, Malaysia / Muhamad Fares Ameran - Ameran, Muhamad Fares (2019)
Perlis, Malaysia currently develop with various types of industrial and agricultural activities which resulted atmospheric and soil pollutants problems. Tree bark is an example of biomonitoring technique which suitable and effective to evaluate the air pollution levels in targeted area. Tree barks (Tectona grandis sp.) and nearby topsoil samples were used to evaluate the selected heavy metals (As, Fe, Cd, Co, Cr, Cu, Mn, Ni, Pb and Zn) in Perlis area. Eighteen samples of tree bark and topsoil each were collected from same station at Perlis area. Both samples were analysed using energy dispersive X-Ray fluorescence (EDXRF) spectrometer and evaluated with inductively coupled plasma mass spectromenter (ICPMS). The results concentration of elements shows that As, Fe, Cr, Pb and Zn recorded above the natural level. In addition, the heavy metal pollution level in atmospheric was evaluted using assessment through the calculatation of enrichment factor (EF), geoaccumulation index (Igeo) and pollution index (PI). Average EF values was used to evaluate tree bark samples that indicates all location had polluted. Meanwhile, Igeo evaluation shows only Fe, Co, Cr, Cu, Mn, Ni and Zn were categorised in uncontaminated soil. While overall pollution by pollution index (PI) calculated heavy metal in tree bark and topsoil sample were originated from natural sources except station 18 of topsoil sample. Besides that, principle component analysis (PCA) and cluster analysis (CA) were used to determine possible sources of heavy metal in atmosphere and topsoil. Analysis of tree bark and topsoil shows the heavy metal pollutants sources were possibly from transportation, agriculture, industrial and natural sources. The overall results obtained clearly shows tree bark {Tectona grandis sp.) is suitable to be used as biomonitoring for monitoring atmospheric pollutants.